Tinjauan Yuridis Perkara Permohonan Akta Kematian yang Berkaitan dengan Asas Persona Standi in Judicio (Studi Kasus Putusan Nomor 93/Pdt.P/2019/PN Mgg) - Nurdayanti, Annisa; Anggraini, Ika Ari; Ramadhani, Sarah Budi; Heniyatun, Heniyatun (Borobudur Law Review, 2019)
Inheritance law is a part of family law, which is very closely related to the scope of human life. In the case of someone's death, registration must be carried out at the Civil Registry office, and those who are entitled to make arrangements are heirs. But in case Number 93 / Pdt.P / 2019 / PN Mgg, registration is carried out by people who do not have a legal position against the heir. The purpose of writing this article is to analyze the application of the principle of persona standi in judicio, zaakwarneming, and the position of the property of people who do not have children. The research method used is normative juridical with the statue and conceptual approach. The results showed that the case for the death certificate application filed by the applicant could not be granted because it would have long legal consequences related to inheritance.